Excess Anterior Mitral Leaflet in a Patient With Hypertrophic Obstructive Cardiomyopathy and Systolic Anterior Motion. Issue 18 (5th May 2015) - Numata, Satoshi; Yaku, Hitoshi; Doi, Kiyoshi; Yamazaki, Sachiko; Yamamoto, Tsuneyasu; Kobayashi, Takuma; Manabe, Kaichiro; Kawazoe, Kohei
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.